2018
DOI: 10.1007/s10853-018-2310-8
|View full text |Cite
|
Sign up to set email alerts
|

Surface characterization of nitrogen-doped Nb (100) large-grain superconducting RF cavity material

Abstract: (100) oriented niobium (Nb) crystals annealed in the vacuum conditions close to that used in mass production of 1.3 GHz superconducting radio-frequency cavities for linear accelerators, and treated in nitrogen at a partial pressure of 0.04 mbar at temperatures of 800 °C and 900 °C have been studied. The surfaces of the nitrogen-treated samples were investigated by means of various surface-sensitive techniques, including grazing-incidence X-ray diffraction, X-ray photoemission spectroscopy and scanning electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 40 publications
3
10
1
Order By: Relevance
“…However, at 500°C a new layer with a thickness of 1.41 nm was formed between NbO and Nb. The electron density of this layer is similar to the theoretically calculated value for the β-Nb 2 N phase, which is known to precipitate upon high-temperature treatments in a N 2 atmosphere [10,14]. Therefore, it can be concluded that the layer relates to the presence of a possible Nb x N y compound underneath the oxide layer, as the presence of typical β-Nb 2 N precipitates at the surface was not observed by SEM [ Fig.…”
Section: Stepwise Annealing and Interstitialsupporting
confidence: 77%
See 4 more Smart Citations
“…However, at 500°C a new layer with a thickness of 1.41 nm was formed between NbO and Nb. The electron density of this layer is similar to the theoretically calculated value for the β-Nb 2 N phase, which is known to precipitate upon high-temperature treatments in a N 2 atmosphere [10,14]. Therefore, it can be concluded that the layer relates to the presence of a possible Nb x N y compound underneath the oxide layer, as the presence of typical β-Nb 2 N precipitates at the surface was not observed by SEM [ Fig.…”
Section: Stepwise Annealing and Interstitialsupporting
confidence: 77%
“…Furthermore, a contribution from two peaks at binding energies of 204.3 and 207.0 eV is detected, which can be attributed to a NbN x O y phase, supported by the presence of a peak in N 1s core level [Figs. 8(c) and 8(d)] at the binding energy of ∼397.5 eV, which corresponds to Nb bound to N in niobium nitrides and oxynitrides as reported for the nitrogen-doped niobium samples [10]. The peak at a higher binding energy in the N 1s region at ∼400 eV is assigned to the adsorbed N on the surface.…”
Section: Stepwise Annealing and Interstitialsupporting
confidence: 59%
See 3 more Smart Citations